The genus Orieosia Bucsek, 2012 also found in New Guinea, with description of two new species (Lepidoptera: Erebidae, Arctiinae, Lithosiini) - Vos, Rob De (Zootaxa, 2022)
The genus Orieosia Bucsek, 2012 appears to be present in New Guinea too. Four species have been discovered in New Guinea to belong to this formerly believed to be Oriental genus. Two already known species, Lambula hypopolius Rothschild, 1916 and Utriculofera tetrastigmata Rothschild, 1916, are transferred to the genus Orieosia Bucsek, 2012. Orieosia stenoptera spec. nov. and O. albigrisea spec. nov. are described as new to science. Nomenclatorial confusion with Holocraspedon hypopolius (Rothschild, 1916) is discussed.